2019
DOI: 10.1038/s41385-018-0130-4
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary group 2 innate lymphoid cells: surprises and challenges

Abstract: Group 2 innate lymphoid cells (ILC2s) are a recently described subset of innate lymphocytes with important immune and homeostatic functions at multiple tissue sites, especially the lung. These cells expand locally after birth and during postnatal lung maturation and are present in the lung and other peripheral organs. They are modified by a variety of processes and mediate inflammatory responses to respiratory pathogens, inhaled allergens and noxious particles. Here, we review the emerging roles of ILC2s in pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 206 publications
(289 reference statements)
4
66
0
Order By: Relevance
“…Numerous studies suggest that mepolizumab (anti-IL-5 monoclonal antibody) treatment reduces the requirement for oral steroids in severe eosinophilic asthma [96,97]. Furthermore, there are known links between innate type 2 inducers and mediators IL-33, IL-25 and TSLP (thymic stromal lymphopoietin), and type 2 innate lymphoid and T-helper cells and steroid resistance [98][99][100]. Antibodies against these factors may prove to be somewhat effective in severe disease [4,99,101].…”
Section: Biologicsmentioning
confidence: 99%
“…Numerous studies suggest that mepolizumab (anti-IL-5 monoclonal antibody) treatment reduces the requirement for oral steroids in severe eosinophilic asthma [96,97]. Furthermore, there are known links between innate type 2 inducers and mediators IL-33, IL-25 and TSLP (thymic stromal lymphopoietin), and type 2 innate lymphoid and T-helper cells and steroid resistance [98][99][100]. Antibodies against these factors may prove to be somewhat effective in severe disease [4,99,101].…”
Section: Biologicsmentioning
confidence: 99%
“…These studies demonstrated that the protective effects of IL‐33 were significantly diminished in the absence of ILC2s . However, these mice were also depleted of other CD90 expressing cells including T reg cells, which may also be critical for this renoprotection . Furthermore, a complex bidirectional relationship exists between ILC2s and T reg .…”
Section: Ilc2s As a Potential Cellular Therapy In Renal Injurymentioning
confidence: 97%
“…However, these mice were also depleted of other CD90 expressing cells including T reg cells, which may also be critical for this renoprotection . Furthermore, a complex bidirectional relationship exists between ILC2s and T reg . This concept is supported by studies examining the IL233 hybrid cytokine .…”
Section: Ilc2s As a Potential Cellular Therapy In Renal Injurymentioning
confidence: 98%
“…ILC2 initiates and maintains the adaptive Th2 immune response which can be activated by IL-25, IL-33 and TSLP. 40 To determine how ITGB4…”
Section: Increased Expression Of Tslp In Itgb4deficient Airway Epitmentioning
confidence: 99%